anonymous
  • anonymous
Solve the Linear System using the elimination method or the Substitution method 3x+4y=4 3x+y=10
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Equations given are 4x = 3y + 4 ------------------->(1) 3x = 4y + 10 ------------------->(2) As, we see from equations (1) and (2) coefficients of x or y are not same. So, to make the coefficients of x same we multiply equation (1) by 3 and equation (2) by 4. 3(4x = 3y + 4) ------------>(1) 4(3x = 4y + 10) ------------->(2) We'll get 12x = 9y + 12 -------------------->(1) 12x = 16y + 40 -------------------->(2) Now, as you can see cofficients of x are same in both equations, but they both are positive. So, to eliminate x if we make one negative we'll eliminate x and we can then solve for y. To do that multiply equation (2) by -1 and then add. 12x = 9y + 12 ---------------(1) -1(12x = 16y + 40) -----------------(2) We'll get 12x = 9y + 12 -------------(1) -12x = -16y - 40 --------------(2) _______________ 0= -7y - 28 7y +7y (add 7y on both sides of equation) _________________ 7y = -28 (7y)/7 = -28/7 (divide both sides by 7) y =-4 (answer) Now, substitute the value of y in original equation (1) and solve for x. 4x = 3y + 4 (given equation) 4x = 3(-4) + 4 (since, y = 4) 4x = -12 + 4 4x = -8 (4x)/4 = -8/4 (divide both sides by 4) x = -2 (answer)
anonymous
  • anonymous
this is a different way the i learned and much longer is there a different wayv
anonymous
  • anonymous
?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
You can also solve by using the Substitution method, if you prefer it. 3x+4y=4 3x+y=10 Since there is nothing being multiplied by y in the second equation, we'll solve for y there. It makes it easier because all we have to do is subtract 3x. 3x+4y=4 y=-3x+10 Since we have solved for y, you can plug in -3x+10 in the first equation. 3x+ 4(-3x+10)=4 Using the distributive property, we now get 3x-12x +40=4 Now combine like terms -9x=-36 And if we divide by -9 to solve for x, you see x=4. Now choose either of the equations and plug in 4 for x and solve for y.

Looking for something else?

Not the answer you are looking for? Search for more explanations.